Beyond Compliance: The Role of Green Economy and Digitalization in Enhancing MSMES’ Tax Contribution - Annisaa, Restu Hanin; Azis, Azolla Degita; Sukmawati, Aegisia; Ramalia, Aminah (Jurnal Sains Sosio Humaniora, 2026)
This study aims to analyze the relationship between the green economy, the digitalization of MSMEs, tax compliance, and the tax contributions of MSMEs. This study employs a quantitative approach using data collected via a questionnaire from a sample of 109 MSMEs in Indonesia. The data analysis technique used is Partial Least Squares Structural Equation Modeling (PLS-SEM) to test the relationships among the variables. The results show that the green economy and the digitalization of MSMEs have a positive effect on MSME tax compliance, and tax compliance has a significant effect on MSME tax contributions. The findings of this study provide practical implications for policymakers and tax authorities to encourage MSME adoption of green economic practices and digital technologies as strategic instruments for improving tax compliance. In addition, the results suggest that strengthening digital transformation programs and sustainability-oriented initiatives among MSMEs can contribute to increasing tax revenues and supporting sustainable economic development. This study has a limitation in that it still uses digitalization in a general sense, without specifying the form of digitalization used. Future research is expected to focus on the digitalization of MSME record-keeping or the digitalization of the MSME tax system.